2017
DOI: 10.3847/1538-4357/aa9658
|View full text |Cite
|
Sign up to set email alerts
|

Erratum: “Standing on the Shoulders of Dwarfs: The Kepler Asteroseismic LEGACY Sample. I. Oscillation Mode Parameters” (2017, ApJ, 835, 172)

Abstract: The advent of space-based missions like Kepler has revolutionized the study of solar-type stars, particularly through the measurement and modeling of their resonant modes of oscillation. Here we analyze a sample of 66 Kepler main-sequence stars showing solar-like oscillations as part of the Kepler seismic LEGACY project. We use Kepler short-cadence data, of which each star has at least 12 months, to create frequency power spectra optimized for asteroseismology. For each star we identify its modes of oscillatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
205
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 92 publications
(215 citation statements)
references
References 107 publications
10
205
0
Order By: Relevance
“…Our initial sample consists in the 61 solar-like oscillating stars observed by Kepler analyzed in Appourchaux et al (2012) complemented by 26 dwarfs from the LEGACY sample of 66 stars in Lund et al (2017) and not included in Appourchaux et al (2012). These 87 stars containing main sequence and slightly more evolved stars are listed in Table 1, where the total length of the observations and the associated duty cycles are given as well.…”
Section: Observationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our initial sample consists in the 61 solar-like oscillating stars observed by Kepler analyzed in Appourchaux et al (2012) complemented by 26 dwarfs from the LEGACY sample of 66 stars in Lund et al (2017) and not included in Appourchaux et al (2012). These 87 stars containing main sequence and slightly more evolved stars are listed in Table 1, where the total length of the observations and the associated duty cycles are given as well.…”
Section: Observationsmentioning
confidence: 99%
“…The objective here is to make progress in the understanding of the physical mechanisms responsible for the perturbations inducing the variability of the p-mode oscillations with magnetic activity. We started with a sample of 87 solar-like pulsating stars observed by Kepler and for which the peak-fitting analysis of the individual modes can be found in the literature (Appourchaux et al 2012;Lund et al 2017). The reason for selecting this sample is threefold: (1) it allowed us to study stars from the three following categories depending to their seismic and spectroscopic properties: the simple stars, the F-type stars, and the mixedmode stars (for more details, see Appourchaux et al 2012); (2) the characterization of the individual modes of these stars is already available and their fundamental stellar properties determined (Mathur et al 2012;Metcalfe et al 2014;Creevey et al 2017;Silva Aguirre et al 2017); and (3) these stars were observed in short cadence (SC; for more details, see Gilliland et al 2010) for at least 1 yr.…”
Section: Introductionmentioning
confidence: 99%
“…6 The sound of the bells (their eigenfrequencies) does not depend on how the bells are rung (Baade, 1992). 7 Note, however, that in many cases the studies of solar-type pulsators seem to be limited to using the frequency separations and frequency maximum to derive the astrophysical parameters of the stars, using the so-called "scaling relations" (Lund et al, 2017). 8 However, the dependence of the period spacing on the thickness of the outer envelope of DA and DB WDs is generally weaker than its dependence upon the effective temperature and the stellar mass (Tassoul et al, 1990).…”
mentioning
confidence: 99%
“…The agreement between observations and models is very satisfactorily. Moreover, all 1D models have global stellar parameters determined from minimizing the differences between observed and adiabatically computed oscillation frequencies [14], calibrated max(p t ) values, depth-dependent functional forms of the turbulent-velocity anisotropy Φ and T − τ relations as suggested by 3D simulations [15,16].…”
Section: Resultsmentioning
confidence: 99%
“…We use LEGACY [14] linewidths and frequencies of selected solar-type Kepler stars, together with 3D hydrodynamical simulation results [15,16], for calibrating the global stellar and nonlocal convection parameters in 1D stability computations. Additionally to exploiting the seismic diagnostic of observed oscillation frequencies, linewidth measurements provide further diagnostic information about the physical processes prevailing in the outer superadiabatic boundary layers where convective transport becomes inefficient.…”
Section: Introductionmentioning
confidence: 99%